CLINICAL PHARMACOLOGICAL SERVICE IN OPTIMIZATION OF THE PHARMACOLOGICAL SUPPORT AT THE INITIAL STAGE OF THE PEDIATRIC CARE - M.M. Sadykov; L.S. Grishina; R.R. Niyazov; L.E. Ziganshina (Педиатрическая фармакология, 2008)
Assisted by АВС/VEN analysis, the article evaluates the efficiency of the medication consumption in the day patient facility of the children's health center for 4 years, while providing the beneficial categories of the children's population with the necessary medications. Having analyzed the efficiency of the acute respiratory viral infection pharmacotherapy by the indices of the who medication prescription, the authors identified the leading role of the clinical pharmacological service in the optimization of the pharmacological support at the initial stage of the pediatric care pertaining to the reasonable prescription of medications and impact on the inefficient variants of their application.Key words: clinical pharmacology, children, children's health center, day patient facility, medication, pharma-cotherapy.